1996
DOI: 10.2307/2171787
|View full text |Cite
|
Sign up to set email alerts
|

Bargaining and Value

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.We present and analyze a model of noncooperative bargaining among n participants, applied to situations describable as games in coalitional form. This leads to a unified solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
258
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 290 publications
(268 citation statements)
references
References 25 publications
(11 reference statements)
8
258
0
2
Order By: Relevance
“…In the literature various implementations of the Shapley value can be found, see e.g. Gul (1989), Hart and Mas-Colell (1996) and Pérez-Castrillo and Wettstein (2001). In this section we adapt the last mechanism and obtain the following mechanism that implements any egalitarian Shapley value as the unique subgame perfect equilibrium outcome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature various implementations of the Shapley value can be found, see e.g. Gul (1989), Hart and Mas-Colell (1996) and Pérez-Castrillo and Wettstein (2001). In this section we adapt the last mechanism and obtain the following mechanism that implements any egalitarian Shapley value as the unique subgame perfect equilibrium outcome.…”
Section: Methodsmentioning
confidence: 99%
“…Actually, only few works address the issue of implementing mixed solutions like the egalitarian Shapley values. Hart and Mas-Colell (1996) discussed a generalized version of their multilateral bargaining game and found that, for some θ ∈ (0, 1), if the proposer drops out with probability (1−ρ)θ, whereas each responder drops out with equal probability (1 − ρ)(1 − θ)/(s − 1), 12 then the game implements the corresponding egalitarian Shapley value with respect to θ in stationary subgame perfect equilibria. However, we like to point out that this result only obtains the egalitarian Shapley value as the equilibrium outcome in expected terms rather than in actual terms, as the game requires an ex ante probability distribution for players to be proposer.…”
Section: Methodsmentioning
confidence: 99%
“…Gul (1989), Hart and Mas-Colell (1996) and Pérez-Castrillo and Wettstein (2001). A cooperative game solution is (strategically) implemented if for every cooperative game one defines an associated strategic or extensive form game (a mechanism) such that applying some strategic solution, for example the subgame perfect equilibrium, always yields payoff outcomes according to this cooperative solution.…”
Section: Methodsmentioning
confidence: 99%
“…One may conjecture, that, as in Hart and Mas-Colell (1996a), as ρ approaches 1 the SP equilibrium payoffs approach a Maschler-Owen (1992) consistent NTU value of (N, V G,σ ). It is not difficult to see that this is indeed the case if, for every S, the limit of the SP equilibrium payoffs of S lies in a smooth piece of the efficient boundary of 8 V G,σ (S).…”
Section: Equilibria With Fixed Threatsmentioning
confidence: 97%
“…There is another source of inspiration for the PC approach: the bargaining procedure formulated by ourselves (Hart and Mas-Colell, 1996a) for the context where the underlying reality is a game in coalitional form. The sequential nature of the announcements and proposals we take from there, along with the idea that a rejected proposer becomes passive for the rest of the game (with some probability).…”
Section: Introductionmentioning
confidence: 99%